Surface modification of a-plane sapphire substrates and its effect on crystal orientation of ZnTe layer. (19th December 2016) - Nakasu, Taizo; Sun, Wei-Che; Kobayashi, Masakazu
Abstract: Domain structures of ZnTe layers grown on a -plane sapphire substrates were investigated by changing the crystallographic properties of the surface and interface. Pole figure images were obtained and we investigated the domain structure in the grown film and the orientation relationships between films and substrates. It was confirmed that two kinds of {111} domains were oriented by annealing the buffer layer at 350 °C, while the (100) domain was obtained by annealing the buffer layer at 300 °C. From the results of the rocking curve measurement, the introduction of a step-terrace surface through the high-temperature treatment of the substrate resulted in an improved crystallographic quality. However, it did not affect the domain structure in the layer. The introduction of an off-angle on the substrate surface resulted in the formation of a single (111) domain layer. These crystallographic features were mainly affected by the surface atom arrangement of the sapphire substrate and its chemical nature.